DIRECT EXPRESSIONS FOR OGATA LEAD-LAG DESIGN METHOD USING ROOT LOCUS - Teixeira, MCM (Institute of Electrical and Electronics Engineers (IEEE), 1994)
Direct expressions for the design of a lead-lag continuous compensator using the root locus method and the procedure described in the 1970 and 1990 books by Ogata are presented. These results are useful in the Ogata design method because they avoid the geometrical determination of poles and zeros, making it easier to create a computer-based design.